Efficient assembly of iminodicarboxamides by a truly four component reaction - Khoury, Kareem (2012)
A truly 4-component reaction! In analogy to a galaxy consisting of millions of stars a multicomponent reaction scaffold can result in millions of compound variations. The MCR of α-amino acids, oxocomponents, isocyanides and primary or secondary amines is such a high-number high-diversity reaction providing an enormous potential for drug discovery or catalyst screening.